Early Childhood Risk Exposures and Inflammation in Early Adolescence - O’Connor, Thomas G (Brain Behav Immun, 2019)
There is now reliable evidence that early psychosocial stress exposures are associated with behavioral health in children; the degree to which these same kinds of stress exposures predict physical health outcomes is not yet clear. We investigated the links between economic adversity, family and caregiving stress in early childhood and several markers of immune function in early adolescence. The sample is derived from the Family Life Project, a prospective longitudinal study of at-risk families. Socio-demographic and psychosocial risks have been assessed at regular intervals since the children were first assessed at 2 months of age. When the children were early adolescents, we conducted an in-depth health assessment of a subsample of families; blood samples were collected from venipuncture for interleukin(IL)-6, Tumor Necrosis Factor (TNF)-alpha, and C-reactive protein (CRP), as well as glucocorticoid resistance. Results indicated limited but reliable evidence of an association between early risk exposure and inflammation in adolescence. Specifically, caregiver depressive symptoms in early childhood predicted elevated CRP almost a decade later, and the prediction was significant after accounting for multiple covariates such as socio-economic adversity, health behaviors and body mass index. Our findings provide strong but limited evidence that early stress exposures may be associated with inflammation, suggesting one mechanism linking early stress exposure to compromised behavioral and somatic health.